Unusual presentation of bladder paraganglioma: Comparison of 131I MIBG SPECT/CT and 68Ga DOTANOC PET/CT - Tarun Jain; Rajender Basher; Nitin Gupta; Jaya Shukla; Shrawan Singh; Bhagwant Mittal (World Journal of Nuclear Medicine)
Extraadrenal chromaffin cell-related tumors or paragangliomas are rare, especially in the bladder, accounting for less than 1% of cases. We report a 16-year-old boy who presented with hematuria and paroxysmal headache and was found to have a prostatic growth infiltrating the urinary bladder on anatomical imaging. Iodine-131 (131I) metaiodobenzylguanidine (MIBG) whole-body scanning and subsequently gallium-68 (68Ga) DOTANOC positron emission tomography/computed tomography (PET/CT) were performed. The MIBG scan revealed a non-tracer-avid soft-tissue mass, while DOTANOC PET/CT revealed a tracer-avid primary soft-tissue mass involving the urinary bladder and prostate with metastasis to the iliac lymph nodes. He underwent surgical management; histopathology of the surgical specimen revealed a bladder paraganglioma, whereas the prostate was found to be free of tumor.